Interspecific and temporal variation of condensed tannins and cyanide concentrations in potential dietary sources of extralimital giraffes (Giraffa camelopardalis) in the Karoo - Marais, Eugene (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.